2014
DOI: 10.21608/jssae.2014.49103
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Mower for Grass Harvesting

Abstract: This study aims to develop, construct and field evaluate small-scale mower for grass harvesting. The mower machine is fabricated from local materials which redesign and modify the cutting drum. The results indicated, reducing friction and improved the mower performance, reduce noise, maximize cutting efficiency and minimize energy requirements. The results can be summarized as follows: Maximum effective field capacity of 587.4 m 2 /h was obtained with forward speed of 2.16 km/h, cutting height of 2 cm and cutt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
(1 reference statement)
0
1
0
Order By: Relevance
“…The primary factors that affect the cutting performance of a drum cutter include its structure and operating parameters. In some studies, it has been shown that harvest loss is related to blade shape [2][3][4][5], cutter surface [6,7], and cutter speed [8][9][10][11]. The key factors affecting the shape and size of the cutting area are cutter size, blade arrangement, and cutting speed ratio [12][13][14], all of which should be thoroughly analyzed and taken into account for design.…”
Section: Introductionmentioning
confidence: 99%
“…The primary factors that affect the cutting performance of a drum cutter include its structure and operating parameters. In some studies, it has been shown that harvest loss is related to blade shape [2][3][4][5], cutter surface [6,7], and cutter speed [8][9][10][11]. The key factors affecting the shape and size of the cutting area are cutter size, blade arrangement, and cutting speed ratio [12][13][14], all of which should be thoroughly analyzed and taken into account for design.…”
Section: Introductionmentioning
confidence: 99%